Topical Polyethylene Exposure Induces Conjunctival Inflammation and Early Meibomian Gland Alterations in Wistar Rats - Felicia Yoshe; Yudhiakuari Sincihu; Imelda Theodora; Titiek Ernawati; L. Suwandito (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Nanoplastics are plastic particles smaller than 1000 nm formed from plastic degradation, including polyethylene (PE) These particles can enter the eye through environmental exposure or topical products and may induce oxidative stress, inflammation, and Meibomian gland dysfunctionEvidence regarding ocular toxicity from topical nanoplastic exposure remains limited. To evaluate the effects of topical polyethylene nanoplastic exposure on ocular surface inflammation and Meibomian gland histology. This experimental post-test only study used male Rattus norvegicus Wistar rats receiving topical polyethylene nanoplastic eye drops. Histopathological analysis with Hematoxylin–Eosin staining assessed PMN infiltration, normal Meibomian acini, acinar width, and gland obstruction. PMN infiltration in the palpebral conjunctiva increased significantly (p=0.014), while normal Meibomian acini decreased significantly (p=0.000). Other parameters showed no significant differences. Topical polyethylene nanoplastic exposure induces conjunctival inflammation and early Meibomian gland alterations.